(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, we have thought about the artists who took place in the literary environment of Bukhara and created. We have presented opinions about the scientific heritage and creativity of one of such creators, Sayyid Poshhohoja, and his place in the literary environment of Movarunnahr.